Analysis of Calsium (Ca) and Potassium (K) Levels in Candlenut Shells (Aleurites moluccana Willd) - Megawati T. H. Romu; Siti Nuryanti; Siti Aminah (Jurnal Akademika Kimia, 2020)
Candlenut shell (Aleurites moluccana Willd) is a waste produced from processing candlenut plants with a fairly hard texture. The use of candlenut shells as fertilizer, especially in Central Sulawesi, has not been done so much. The aim of this study was to determine the levels of calcium (Ca) and potassium (K) in candlenut shells. Calcium and potassium levels were determined using an atomic absorption spectrophotometer (AAS). The results show that the average calcium level in the candlenut shell is 0.315 ± 0.09%, while the average potassium level is 0.090 ± 0.01%. The results of Ca and K in candlenut shell are expected to be used as raw material for fertilizer production.